Students' Speaking Anxiety of Learning English Speaking Skills at Grade X of SMA Swasta Daerah Kisaran: Penelitian - Syaipullah Akbar Sinaga; YenYen Kezia Agustin; Annisa Zahra; Nabilah Amelia Putri; Wan Ririn Aulya Putri (Jurnal Pustaka Cendekia Pendidikan, 2026)
This study investigates students' speaking anxiety in English speaking skill learning at Grade X of SMA Swasta Daerah Kisaran. Speaking anxiety is a common psychological barrier that inhibits students' oral performance in the English as a Foreign Language (EFL) context. This qualitative descriptive study aimed to identify the dominant causes of speaking anxiety, describe coping strategies employed by students, and analyze the correlation between anxiety levels and speaking fluency during individual presentations. Data were collected through the Foreign Language Classroom Anxiety Scale (FLCAS) questionnaire, semi-structured interviews, and classroom observation of 15 selected Grade X students. The findings reveal that 40% of participants demonstrated severe anxiety levels (scoring 8-10 on the anxiety scale). The dominant internal factor was fear of making mistakes, affecting 10 out of 15 students. External factors such as peer pressure, audience gaze, and fear of negative evaluation significantly amplified students' anxiety. These results align with Horwitz et al.'s (1986) FLCAS framework encompassing communication apprehension, test anxiety, and fear of negative evaluation. The study recommends that English teachers adopt low-stakes interactive methods, reduce immediate corrective feedback, and cultivate a supportive classroom culture to lower the affective filter and enhance students' speaking confidence.